Revision of the genus Xizangiana Sherwood, Li & Zhang, 2022, with descriptions of five new species (Araneae: Gnaphosidae) - Liu, Bo; Wang, Luyu; Zhang, Feng (Zootaxa, 2023)
The genus Xizangiana Sherwood, Li & Zhang, 2022 is revised. Two known species and five new species from China are described and illustrated: Xizangiana linzhiensis (Hu, 2001), X. rigaze (Song, Zhu & Zhang, 2004), X. benae Liu & Zhang, sp. n. (♂♀), X. longlin Liu & Zhang, sp. n. (♂♀), X. namchabarwa Liu & Zhang, sp. n. (♂♀), X. shenxian Liu & Zhang, sp. n. (♂♀) and X. xiangbi Liu & Zhang, sp. n. (♂♀). Two new combinations from India, Xizangiana pawani (Gajbe, 1993) comb. n. (ex. Urozelotes Mello-Leitão, 1938) and X. sedula (Simon, 1897) comb. n. (ex. Poecilochroa Westring, 1874), are proposed. The subfamily placement of Xizangiana is discussed and the records of all the species is mapped.